TiO2 NPs/h-BN: Preparation and catalytic activities of a novel AP catalyst - Zhao, Jun; Deng, Nengmei (Frontiers in Chemistry, 2022)
The thermal decomposition performance of an oxidizer directly determines the thrust and specific impulse properties of the solid propellant. Hexagonal boron nitride (h-BN) has the characteristics of high catalytic activity and good stability, which can improve the heat release and decomposition temperature of the oxidant, and then improve the energy performance of the propellant. In this study, a novel hybrid material TiO2 NPs/h-BN was successfully prepared by in situ growth, and it was found that when 5 wt.% TiO2 NPs/h-BN was added, the initial decomposition temperature of ammonium perchlorate (AP) decreased by 67.6°C. Due to the addition of TiO2, the gap between the h-BN layers as well as the specific surface increased, which optimized its thermocatalytic performance, and it also proposed a catalytic mechanism for the thermal decomposition process of AP.